Measuring learning outcomes of entrepreneurship education using structural equation modeling - Inna Kozlinska; T\~onis Mets; Kärt R\~oigas (Administrative Sciences, 2020)
This paper empirically substantiates a novel tripartite framework for measuring learning outcomes of entrepreneurship education (EE) by employing structural equation modeling. Three types of learning outcome are estimated-cognitive, skill-based, and affective-following Bloom's (1956) taxonomy of educational objectives. The study is based on a sample of 249 imminent and recent Bachelor-level graduates from the leading universities of Estonia. The key fit, reliability, and validity indicators show statistically that the tested framework can serve as an instrument for measuring the learning outcomes of EE. This novel instrument may also serve as an alternative to entrepreneurial intention-based models very frequently used in EE to evaluate the learning outcomes. The studied interrelationships demonstrate that (1) the affective outcomes correlate significantly with the cognitive outcomes (r = 0.273, p < 0.001) and with the skill-based (r = 0.368, p < 0.001) outcomes; a correlation between the cognitive and skill-based outcomes is also significant and comparatively high (r = 0.602, p < 0.001); (2) the learning outcomes explain more variance in the cognitive and skill-based outcome constructs (44.7% and 81.0%, accordingly) than in the affective outcome construct (16.7%). Conclusions and implications for entrepreneurship educators and researchers are discussed.
Keywords: 350; entrepreneurship education; learning outcomes; structural equation modeling